The Relationship Between R&D Investment and Firm Profitability Under a Three-Stage Sigmoid Curve Model: Evidence From an Emerging Economy - Yang, Kuo-Pin; Chiao, Yu-Ching; Kuo, Chih-Chung (IEEE transactions on engineering management, 2010)
The relationship between investment in research and development (R&D) and firm performance has been the subject of numerous academic investigations, but the findings of these investigations have varied greatly, with research revealing a number of different patterns in the R&D-performance relationship. This inconsistency may be partly attributable to the failure of the commonly used linear modeling method to capture the full dynamics of the R&D-performance relationship. Based on the sigmoid (S) curve paradigm, as well as on other economic foundations, this study proposes the use of a three-stage S-curve model to help reconcile the disparities in the literature. This S-curve model shows that the relationship between R&D intensity and firm profitability is nonlinear, with the slope negative at low levels (stage 1), positive at medium levels (stage 2), and negative again at high levels of R&D investment (stage 3). Empirical evidence from a sample of 377 publicly listed Taiwanese high-tech manufacturing firms and 179 nonhigh-tech firms, examined during the period between 2000 and 2007, confirmed our proposed model. This study not only establishes a relationship pattern that differs from that shown in past studies, but also has important managerial implications for R&D managers and important policy implications for governments.